Carcerality and the legacies of settler colonial punishment in Nairobi - Pfingst, Annie (Punishment & society, 2021)
From the beginning of its colonial settlement in Kenya, the British administration criminalized Kenyans. Even now, colonial modes of punishment, incarceration, closure, interrogation, curfew, confiscation, separation, displacement, and detention without trial are deeply embedded in the spatial and ideological arrangements of post-colonial Kenya. Initially assumed to herald a rupture from colonial modes of criminalization and punishment, the post-colonial period instead normalized them. Through ethnographic, scholarly, and visual encounters, the paper engages five interconnecting structures that engendered the legacy of a seamless system of control, containment, and punishment evident in the ‘afterlives’ of empire. These are settler colonialism, violence, racism, colonial corporeality, and capitalism. The paper attends to the violence and brutality that endures in the very geographies that were the urban targets of colonial siege and links the carceral practices of settler colonialism and the everyday post-colonial governance of Nairobi’s poor neighbourhoods, encounters with the debris and ruination of empire found in the material and spatial fabric of Mathare. We take up a critical encounter with colonial files to both discern the continuity and lineage of carceral practices and to disrupt the authorial totality and continuity the colonial archive files assembled. The paper includes archival and authored photographs: